2022
DOI: 10.3389/fphys.2022.797268
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Body Composition, Energy Metabolites and Electrolytes During Winter Survival Training in Male Soldiers

Abstract: The aim of this study was to examine changes in body composition, energy metabolites and electrolytes during a 10-day winter survival training period. Two groups of male soldiers were examined: the REC group (n = 26; age 19.7 ± 1.2 years; BMI 23.9 ± 2.7) had recovery period between days 6 and 8 in the survival training, whereas the EXC group (n = 42; age 19.6 ± 0.8 years; BMI 23.1 ± 2.8) did not. The following data were collected: body composition (bioimpedance), energy balance (food diaries, heart rate variab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 39 publications
0
5
0
Order By: Relevance
“…In the RECO group, fat mass first reduced and then stabilized during the recovery period (11.4 ± 5.4, 9.0 ± 5.5, 8.7 ± 4.7 kg; p < 0.001 PRE-MID, MID-POST). More results have been presented in the previous study [10].…”
Section: Resultsmentioning
confidence: 71%
See 1 more Smart Citation
“…In the RECO group, fat mass first reduced and then stabilized during the recovery period (11.4 ± 5.4, 9.0 ± 5.5, 8.7 ± 4.7 kg; p < 0.001 PRE-MID, MID-POST). More results have been presented in the previous study [10].…”
Section: Resultsmentioning
confidence: 71%
“…Severe energy deficit impairs hormonal regulation and disturbs homeostasis in harsh environments [10,11]. Appetite-mediating hormones, leptin and ghrelin, react in acute caloric deprivation [12] and in response to loss of body mass [13].…”
Section: Introductionmentioning
confidence: 99%
“…Thus, it is possible that while standing shooting performance was more engaging task, requiring maintenance of stance and upper body muscle activity to hold the weapon for both groups, prone position enabled impairment in upregulating arousal and attention in sleep-deprived EXP, explaining weakening of the results as compared to CON. Secondly, drastic continued energy deficit and higher physical demands of CON may have had more detrimental effects on fine motor performance, such as shooting performance [ 17 , 29 , 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…Previous cold environment military studies have concentrated on energy expenditure and energy balance [ 7 , 16 , 17 ], protective clothing [ 18 ] and cold weather injuries [ 19 ]. Nykänen et al [ 17 ] has recently reported results of the present study population and setting regarding energy balance and changes in body composition.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation